2012
DOI: 10.1186/1748-5908-7-58
|View full text |Cite
|
Sign up to set email alerts
|

Designing a strategy to implement cost-effective blood transfusion management in elective hip and knee arthroplasties: A study protocol

Abstract: Background Total hip and knee arthroplasties are two of the most commonly performed procedures in orthopedic surgery. Different blood-saving measures (BSMs) are used to reduce the often-needed allogenic blood transfusions in these procedures. A recent large randomized controlled trial showed it is not cost effective to use the BSMs of erythropoietin and perioperative autologous blood salvage in elective primary hip and knee arthroplasties. Despite dissemination of these study results, medical prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
(31 reference statements)
0
24
0
Order By: Relevance
“…We use empirical data here from two previously published studies, which are performed at different moments in time: one involving implementation28 29 and one involving de-implementation30 31 among Dutch orthopaedic surgeons. The implementation study aimed to identify factors influencing the implementation of a step-wise strategy of non-surgical therapy for patients with hip and knee osteoarthritis (OA) (including medication and referral guidelines) before undertaking surgical therapy 14.…”
Section: Empirical Datamentioning
confidence: 99%
“…We use empirical data here from two previously published studies, which are performed at different moments in time: one involving implementation28 29 and one involving de-implementation30 31 among Dutch orthopaedic surgeons. The implementation study aimed to identify factors influencing the implementation of a step-wise strategy of non-surgical therapy for patients with hip and knee osteoarthritis (OA) (including medication and referral guidelines) before undertaking surgical therapy 14.…”
Section: Empirical Datamentioning
confidence: 99%
“…The conclusion of this study was thus that these three BSMs were not cost-effective in elective primary TKA and THA [12]. Annually, TKA are performed in about 20.000 patients and THA in about 26.000 patients [13], so that cost savings might be considerable if BSMs are de-implemented [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Blood salvage includes two modalities: first; intraoperative cell salvage, which is used during surgery in which a patients' blood is collected, washed, concentrated and then re-infused, and second, a device that postoperatively collects, filters and re-infuses autologous wound blood by means of a wound drainage and re-infusion system (So-Osman et al, 2014b). Nowadays, the postoperative wound drainage system is used more commonly in primary arthroplasties opposed to intraoperative cell salvage, which is retained for more complex surgery such as revision arthroplasties (Voorn et al, 2013;Struijk-Mulder et al, 2014;Sikorski et al, 2017). In a recent multicentre RCT, it was concluded that blood salvage was not effective to prevent exposure to allogeneic transfusion or to reduce the number of allogeneic red blood cell units transfused in primary elective THA and TKA and therefore could be considered low-value care (So-Osman et al, 2014a,b).…”
Section: Step 1: the Detection Of Improvement Goalsmentioning
confidence: 99%
“…Step 2: The analysis of current care, target group and setting (problem analysis) In this step, the extent of the de-implementation problem is mapped: how often and in what setting low-value care is used, the persons and patients involved in the PBM elements and the relevant barriers and facilitators that are involved in abandoning the PBM elements (Voorn et al, 2012). The problem analysis of the LISBOA study consisted of two parts.…”
Section: Step 1: the Detection Of Improvement Goalsmentioning
confidence: 99%
See 1 more Smart Citation